SPE Western Regional Meeting 2001
DOI: 10.2118/68844-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dual-Porosity Behavior for Horizontal Wells Draining Heterogeneous Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIn the literature it has been shown that a bilinear flow regime, characterized by a quarter slope line on the logarithmic derivative diagnostic plot, can arise for horizontal wells draining fractured or layered reservoirs with transient dualporosity behavior during the intermediate linear flow period. In the case of layered reservoirs the bilinear flow is a result of the linear flow in the more permeable layer toward the well and of the linear flow from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Horizontal well intersecting a High-Permeability Streak Based on the work by Verga et al (2001), the presence of a high-permeability streak was investigated. Attempting to match real data from Well C, a 100ft-wide and 120ft-thick high-permeability streak with horizontal permeability, k H of 10, 000mD surrounded by a 10mD matrix was modeled with the horizontal well intersecting the streak at mid-point.…”
Section: Dual Layer Formation With Higher-permeability Layer Overlyinmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal well intersecting a High-Permeability Streak Based on the work by Verga et al (2001), the presence of a high-permeability streak was investigated. Attempting to match real data from Well C, a 100ft-wide and 120ft-thick high-permeability streak with horizontal permeability, k H of 10, 000mD surrounded by a 10mD matrix was modeled with the horizontal well intersecting the streak at mid-point.…”
Section: Dual Layer Formation With Higher-permeability Layer Overlyinmentioning
confidence: 99%
“…Verga et al (2001) showed that despite permeability contrasts between layers exceeding two orders of magnitude, bilinear flow could not be reproduced in a reservoir simulation. Instead, it was found that bilinear flow is formed when a high-permeability sub-vertical zone is intercepted by the horizontal well.…”
Section: Introductionmentioning
confidence: 99%